Analisis Keuntungan Pedagang Sayur Keliling Di Kecamatan Samboja Kabupaten Kutai Kartanegara - Doddy Setiawan; H. Juliansyah Juliansyah; Siti Amalia (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
Doddy Setiawan, 2020. Profit Analysis of Mobile Vegetable Traders in Samboja District Kutai Kartanegara under the guidance of Juliansyah and Siti Amalia.            This study aims to analyze and find out whether mobile vegetable traders in Samboja District obtain profit or loss. This study uses primary data with a questionnaire technique conducted that mobile vegetable traders in Samboja District. The analysis used is profit analysis, revenue analysis, cost analysis, and business efficiency. The results showed that mobile vegetable traders in Samboja District gained profits.